THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL ATTITUDE ON FINANCIAL MANAGEMENT OF UMKM IN MARITENGNGAE DISTRICT, SIDENRENG RAPPANG REGENCY - Ina syahidah Haris; Darnawati Darnawati; Ari Ayu (Journal Of Accounting And Finance, 2025)
MSMEs play a significant role in advancing the economy of a region, but MSMEs often face challenges in explaining their contributions concretely and managing daily operations. The purpose of this study is to determine the effect of financial literacy and financial attitudes on MSME financial management. This study uses a quantitative method with an associative approach. The population in this study are Micro, Small, and Medium Enterprises (MSMEs) engaged in the fashion sector in Maritengngae District, Sidenreng Rappang Regency. The sample of this study was selected using the Probability Sampling approach with a sample size of 82 respondents. The data collection technique in this study used a questionnaire. The data obtained were then processed through the SPSS 26 program to test validity and reliability, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test), multiple linear regression analysis, hypothesis testing (Coefficient of determination test and t-test). The results of hypothesis testing in this study indicate that financial literacy and financial attitudes have a positive and significant effect on MSME financial management in Maritengngae District, Sidenreng Rappang Regency. This indicates that the understanding of MSME actors towards financial literacy and financial attitudes will affect the ability of MSME actors in managing finances.